2008
DOI: 10.1152/ajpheart.01072.2007
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme, a mediator of sepsis that produces vasodilation by hydrogen peroxide signaling in an arterial preparation

Abstract: In septic shock, systemic vasodilation and myocardial depression contribute to the systemic hypotension observed. Both components can be attributed to the effects of mediators that are released as part of the inflammatory response. We previously found that lysozyme (Lzm-S), released from leukocytes, contributed to the myocardial depression that develops in a canine model of septic shock. Lzm-S binds to the endocardial endothelium, resulting in the production of nitric oxide (NO), which, in turn, activates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(53 citation statements)
references
References 50 publications
(94 reference statements)
7
46
0
Order By: Relevance
“…Burke and Wolin (5, 6) described a unique pathway by which H 2 O 2 caused vasodilation in a preconstricted pulmonary artery preparation. We showed that a similar pathway participated in the vasodilatory response of Lzm-S in recent experiments (28). In a phenylephrine-constricted carotid artery preparation, we demonstrated that the generation of H 2 O 2 by Lzm-S led to the formation of compound I, a species of catalase that is the product of the metabolism of H 2 O 2 .…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Burke and Wolin (5, 6) described a unique pathway by which H 2 O 2 caused vasodilation in a preconstricted pulmonary artery preparation. We showed that a similar pathway participated in the vasodilatory response of Lzm-S in recent experiments (28). In a phenylephrine-constricted carotid artery preparation, we demonstrated that the generation of H 2 O 2 by Lzm-S led to the formation of compound I, a species of catalase that is the product of the metabolism of H 2 O 2 .…”
mentioning
confidence: 51%
“…Compound I then caused activation of smooth muscle soluble guanylate cyclase (sGC), which subsequently resulted in an increase in guanosine 3Ј,5Ј-cyclic monophosphate (cGMP) and thereby produced vasorelaxation. We further demonstrated that ethanol, an inhibitor of compound I, the peroxidizing agent Aspergillus niger catalase, a competitor of endogenous catalase, and inhibitors of sGCcGMP-protein kinase G (PKG) pathway all prevented the vasodilator effect of Lzm-S (28). Moreover, we showed that the vasodilatory response of Lzm-S was not related to the presence of heavy metals [as performed by Buettner (4)] or to changes in pH or calcium in the organ bath and that denatured Lzm-S did not cause vasodilation in our carotid artery preparation (28).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Also, ferritin light chain 1 (Ftl1) was upregulated in both muscle and aortae, possibly reflecting the presence of oxidized low-density lipoproteins in diabetic endothelium (16). One other transcript dysregulated in both aortic and skeletal muscle endothelium, lysozyme 1 (Lyz1), is involved in the modulation of AGEs (43) and is a vasodilator (27).…”
Section: Discussionmentioning
confidence: 99%